Metabolic Engineering of Escherichia coli for the Production of Xylonate - Cao, Yujin (Public Library of Science, 2013)
Xylonate is a valuable chemical for versatile applications. Although the chemical synthesis route and microbial conversion pathway were established decades ago, no commercial production of xylonate has been obtained so far. In this study, the industrially important microorganism Escherichia coli was engineered to produce xylonate from xylose. Through the coexpression of a xylose dehydrogenase (xdh) and a xylonolactonase (xylC) from Caulobacter crescentus, the recombinant strain could convert 1 g/L xylose to 0.84 g/L xylonate and 0.10 g/L xylonolactone after being induced for 12 h. Furthermore, the competitive pathway for xylose catabolism in E. coli was blocked by disrupting two genes (xylA and xylB) encoding xylose isomerase and xylulose kinase. Under fed-batch conditions, the finally engineered strain produced up to 27.3 g/L xylonate and 1.7 g/L xylonolactone from 30 g/L xylose, about 88% of the theoretical yield. These results suggest that the engineered E. coli strain has a promising perspective for large-scale production of xylonate.